Behaviour and Strength of Headed Shear Stud Connectors - Duratna, Patricia; Bujnak, Jan; Bouchair, Abdelhamid; Bahleda, Frantisek (Communications - Scientific letters of the University of Zilina, 2013)
Headed stud shear connectors are commonly used to transfer longitudinal shear forces across the steel-concrete interface in composite structures. This paper is focused on the experimental and numerical study on the behaviour of this type of connectors. The push-out tests of headed studs, 10 mm in diameter and 50 mm in length, in normal C25/30 concrete with transverse reinforcement were carried out. The experimental study also treated the influence of the connectors spacing, in the longitudinal and transversal directions, and the thickness of the concrete slab on the shear resistance.